EXA 2011 Proceedings of the International Conference on Exotic Atoms and Related Topics (EXA 2011) held in Vienna, Austria, September 5-9, 2011 - Bühler, Paul; Hartmann, Olaf; Marton, Johann; Suzuki, Ken; Widmann, Eberhard; Zmeskal, Johann (Springer Netherlands : Imprint: Springer, 2012)
Proceedings of the International Conference on Exotic Atoms and Related Topics (EXA 2011) held in Vienna, Austria, September 5-9, 2011 P. Bühler, O. Hartmann, J. Marton, K. Suzuki, E. Widmann and J. Zmeskal (Eds.) Now the research in exotic atoms has a remarkable history of more than 50 years. Enormous success in the understanding of fundamental interactions and symmetries resulted from the research on these tiny objects at the femtoscale. This volume contains research papers on recent achievements and future opportunities of this highly interdisciplinary field of atomic, nuclear, and particle physics. The Proceedings are structured according to the conference session topics: Kaon-Nucleus and Kaon-Nucleon Interactions, Antihydrogen and Fundamental Symmetries, Hadronphysics with Antiprotons, Future Facilities and Instrumentation, Low energy QCD. Reprint from Hyperfine Interactions vol. 209, 210 and 211.